Dynamics of prooxidant-antioxidant system in patients with chronic hepatitis c with mixed cryoglobulinemia on a background of various schemes of pathogenetic treatment - Mashko, O.P.; Ryabokon, E.V. (Pathologia, 2013)
It is shown that inclusion of immunomodulating remedy with antioxidant properties (erbisol) into the basic treatment in patients with chronic hepatitis C with mixed cryoglobulinemia can increase the effectiveness of pathogenetic treatment. Against the background of treatment by erbisol in these patients recovery of prooxidant-antioxidant balance and reduce of cytolytic syndrome severity are observed.